2017
DOI: 10.1515/bglass-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

BAG S53P4 putty as bone graft substitute – a rabbit model

Abstract: Bioactive glass (BAG) S53P4 granules represent a bone augmentation biomaterial for the surgical treatment of bony defects, even in challenging conditions such as osteomyelitis. The aim of this eight-week rabbit implantation study was to evaluate the biocompatibility and bone regeneration performance of a BAG S53P4 putty formulation following its implantation into the proximal tibia bone of twenty-eight New Zealand white rabbits. BAG S53P4 putty was compared to BAG S53P4 granules (0.5-0.8 mm) to evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…4 S53P4 putty (48 wt% 500-800 µm granules, 12 wt% 90-250 µm microspheres in a binder mixture of glycerol and polyethylene glycols) showed similar bone regeneration performance as S53P4 granules (500-800 µm) in implantation into rabbit tibia defects. 25 In a clinical follow-up study, the same S53P4 putty was successfully used as bone graft expander in minimally invasive lumbar interbody fusion. 22 A putty consisting of S53P4 granules (500-800 µm) and powder (< 45 µm) increased the pH of broths in antibacterial studies more than granules alone.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…4 S53P4 putty (48 wt% 500-800 µm granules, 12 wt% 90-250 µm microspheres in a binder mixture of glycerol and polyethylene glycols) showed similar bone regeneration performance as S53P4 granules (500-800 µm) in implantation into rabbit tibia defects. 25 In a clinical follow-up study, the same S53P4 putty was successfully used as bone graft expander in minimally invasive lumbar interbody fusion. 22 A putty consisting of S53P4 granules (500-800 µm) and powder (< 45 µm) increased the pH of broths in antibacterial studies more than granules alone.…”
Section: Accepted Articlementioning
confidence: 99%
“…No references were found on modeling for CMCs, though experimental studies o ing process have been reported. Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of bioacti-Novel Bioactive Glass Putty (S53P4) as Bone Graft Expander in Minimally Invasive Lumbosacral Interbody Fusion vity and resorption of BAGs are dependent on the chemical composition, the surrounding pH, the temperature and the surface layers on the glass 24,35) . BAG S53P4 putty used in this study consists of a total of 60% by weight bioactive glass and is a synthetic, osteoconductive and osteostimulative paste-like bone void filler that was found biocompatible in our recent study 31) .…”
Section: Introductionmentioning
confidence: 99%